The Influence of Human Resources Quality on Improving the Performance of Small and Medium Enterprises in Thousand Islands, North Jakarta - Yhonanda Harsono; Otto Fajarianto (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: The aim of this research is to determine that improving the quality of human resources can improve the performance of Small and Medium Enterprises (UKM) in the Seribu Islands community and to formulate quality human resources in order to improve the performance of Small and Medium Enterprises (UKM) in the Thousand Islands community. Design/methodology/approach: The research method that used is descriptive quantitative, uses primary and secondary data types and uses a questionnaire instrument, the number of samples of this study is 100 respondents using the Slovin method in determining the sample. Findings: 2 hypotheses are while the other is accepted Research limitations/implications: Variables considered in this research are human resources quality, performance of Small and Medium Enterprises digital marketing and follows current technology, and business management. The scope of work of the Kepulauan Seribu, North Jakarta. Practical implications: Results show that from the 2 hypotheses proposed Originality/value: This paper is original. Paper type: This paper can be categorized as a research paper